PENGARUH ORIENTASI KEWIRAUSAHAAN DAN INOVASI PRODUK TERHADAP KINERJA UMKM (STUDI KASUS PADA UMKM BAKSO BAKAR DI KECAMATAN RANGKUI KOTA PANGKALPINANG - Marwan; Zamhari; Medinal (Jurnal Progresif Manajemen Bisnis, 2021)
This research was entitled: “Pengaruh Orientasi Kewirausahaan dan Inovasi Produk Terhadap Kinerja UMKM (Studi Kasus Pada UMKM Bakso Bakar di Kecamatan Rangkui Kota Pangkalpinang)”. The background of this research is conducted due to the increasing competition in Bakso Bakar SMEs. The purpose of this study was to determine and examine the effect of entrepreneurial orientation and product innovation on the performance of SMEs, either simultaneously or partially. The method of research is a descriptive quantitative study with a sample size of 30 respondents. This study has three independent variables; entrepreneurial orientation and product innovation. The dependent variable was labeled as a performance of SMEs. Testing instruments are using validity and reliability tests. The data analysis method used in this study is Multiple Linear Regression Analysis using the F-test along with Simple Linear Regression with T-test. Also the researcher use an analysis of the Coefficient of Determination (R2) in order to provide empirically the ability to explaining the dependent by three independence variables simultaneously. The results of the research on the independent variable entrepreneurial orientation (X1) obtained t-count 0.747 < t-table 2.051, and product innovation variable (X2) with t-count 2.545 > t-table 2.051. Therefore, an entrepreneurial orientation does not have a partial effect towards a performance of SMEs and a product innovation has a partial effect towards a performance of SMEs. The results of the F-test show that F-count 13.716 > F-table 3.35. This means that the independent variables (entrepreneurial orientation and product innovation) simultaneously have an affect towards the dependent variable (performance of SMEs). The test results of the Coefficient of Determination (R2) show Adjusted R-Square 0.467 or in other word, that performance of SMEs variable can be explained by entrepreneurial orientation and product innovation variables by 46.7%. While the remaining 0.533 or 53.3% can be explained by other variables outside the research variables.